Contribution of Plasma Proteinase Inhibitors to the Regulation of Activated Protein C in Plasma - Marlar, Richard A; Kressin, David C; Madden, Renee M (Thrombosis and Haemostasis, 1993)
Activated protein C (APC), a serine protease, is regulated in plasma by protease inhibitors. This study was undertaken to determine the role of the major plasma inhibitors in regulating APC in plasma. Kinetic analysis and specific immunoassays for APC-inhibitor complexes were used to determine the inhibitors that form complexes with APC. Of the eight plasma inhibitors investigated, four interact with APC: protein C inhibitor (PCI), α1-proteinase inhibitor (PI), α2-antiplasmin (AP) and C1 esterase inhibitor (C1 Inh). The second order rate constants are: 1.3 × 104 M−1 s−1 (PCI); 15 M−1 s−1 (PI); 410 M−1 s−1 (AP); and <6 M−1 s−1 (C1 Inh), with a relative effectiveness of each inhibitor to inactivate APC in plasma: 49:36:15:<1, respectively. PCI, PI and AP are the major inhibitors of APC in plasma. Low concentrations of APC will be inhibited by PCI with PI and AP playing a secondary role. However, as increasing APC is generated, PI and AP begin to play more important roles as the PCI is consumed.